The early reception of the inconsistency between the two Palinurus episodes in Virgil’s Aeneid - Kozák, Dániel (Acta Classica Universitatis Scientiarum Debreceniensis, 2025)
The paper investigates how ancient commentators and Roman poets recognized and reacted to the inconsistency between the two Palinurus episodes in Virgil’s Aeneid (5,833-871 and 6,337-383). First, I discuss how Servius and Tiberius Claudius Donatus, in their notes on 6,348, remove the inconsistency (regarding divine intervention) by assuming a punctuation different from the one adopted by all modern editors; however, while doing so, they both give rise to another inconsistency between Aeneas’ question and Palinurus’ answer. Second, I examine a passage from Statius’ biography of his father (Silvae 5,3,124–132), where the poet alludes to the Virgilian story apparently according to the version we read in Aeneid 6, but also creatively reproduces some elements of the Virgilian inconsistency. The last text discussed is Ovid’s Remedia amoris, where the poet recalls his vision of Amor Lethaeus at the temple of Venus Erycina; here again, elements of the Virgilian inconsistency are reproduced.